1997
DOI: 10.3109/00365529709028145
|View full text |Cite
|
Sign up to set email alerts
|

Chest Pain and Reappearance of Esophageal Peristalsis in Treated Achalasia

Abstract: The appearance of esophageal peristalsis after forceful dilatation in achalasic patients is frequently associated with persistent or new chest pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
1
11
1
Order By: Relevance
“…Additionally, they demonstrated that these abnormalities were reversible if the outflow obstruction caused by the band was removed. These findings are in part supported by clinical observation of patients treated by either pneumatic dilation or myotomy [7,8,17,18]. Parrilla et al [8] studied 45 patients with achalasia in whom a myotomy had been performed.…”
Section: Natural History Of Esophageal Achalasiasupporting
confidence: 56%
“…Additionally, they demonstrated that these abnormalities were reversible if the outflow obstruction caused by the band was removed. These findings are in part supported by clinical observation of patients treated by either pneumatic dilation or myotomy [7,8,17,18]. Parrilla et al [8] studied 45 patients with achalasia in whom a myotomy had been performed.…”
Section: Natural History Of Esophageal Achalasiasupporting
confidence: 56%
“…It is, however, unclear why certain patients have been observed to recover esophageal function after treatment as in this study and in other case series, 5,6,22,26 whereas others do not. Variants of achalasia exist in which some peristalsis is observed, including vigorous achalasia, characterized by higher-amplitude simultaneous contractions in the distal esophagus in conjunction with a non-relaxing LES, and short-segment achalasia, in which the proximal esophageal segment retains peristaltic activity.…”
Section: Discussionmentioning
confidence: 72%
“…Relief of dysphagia after treatment is assumed to be the result of eliminating this functional obstruction of the distal esophagus. However, although the return of peristalsis after both balloon dilation 5 and Heller myotomy 6 has been described, there is little in-depth analysis of the effect of treatments for achalasia on esophageal body function.…”
mentioning
confidence: 98%
“…It has been reported that propulsive peristaltic contractions could be restored after dilatation in some achalasia patients 7 . We had observed previously the restoration of peristaltic contractions in two achalasia patients after dilatation (ZF Wang, MY Ke, MW Qin, unpubl.…”
Section: Discussionmentioning
confidence: 80%